Child Maltreatment, Fathers, and Adolescent Alcohol and Marijuana Use Trajectories. (2nd March 2020) - Yoon, Susan; Shi, Yang; Yoon, Dalhee; Pei, Fei; Schoppe-Sullivan, Sarah; Snyder, Susan M.
Abstract: Background: Little is known about heterogeneity in developmental trajectories of alcohol and marijuana use among at-risk youth. Objective: This study aims to examine how child maltreatment and father structural factors at different stages in the life course are associated with different patterns of alcohol and marijuana use trajectories. Methods: A sample of youth ( N  = 903) were drawn from the Longitudinal Studies of Child Abuse and Neglect (LONGSCAN). Latent class growth analysis was employed to assess heterogeneity in patterns of adolescent alcohol and marijuana use. In addition, binary logistic regression analysis was performed to examine child maltreatment and father structural factors across different developmental stages as predictors of membership in the identified alcohol and marijuana use trajectory classes. Results: For both alcohol and marijuana use, two distinct latent classes were identified: s table no/low alcohol use (74%) vs. i ncreasing alcohol use (26%); stable no/low marijuana use (85%) vs. increasing marijuana use (15%). Emotional abuse during early childhood and physical abuse during adolescence predicted membership in the increasing alcohol use and the increasing marijuana use classes. The presence of father in the home during early childhood was associated with lower likelihood of being in the increasing alcohol use class. Conclusions: Our findings highlight the importance of understanding the etiology of adolescent substance use through a developmental lens. Screening of exposure to child maltreatment across different developmental stages and interventions promoting father engagement during early childhood might help mitigate the risk of adolescent alcohol and marijuana use.